Estudio de los mecanismos de resistencia asociados al tratamiento con inhibidores de tirosina kinasas en leucemias philadelphia positivas - Ferri, Cristian Alberto (2015)
The resistance to treatment in Chronic Myeloid Leukemia may be due, between others, to mutations in the BCR-ABL1, overexpression of Src-kinases or down-regulation of onco-suppressors genes. The presence of the BCR-ABL1 in Acute Lymphoblastic Leukemia (ALL) is associated with poor prognosis; therefore more aggressive protocols were developed including tyrosine kinase inhibitors (TKI).\nThe hypothesis of this study was to determine if early mutations detection in BCR-ABL1, and expression of LYN and PTEN genes would be involved in treatment resistance.\nUsing high resolution melting and ARMS-qPCR the detection of mutations was increased in 16% with respect to direct sequencing. The analysis of dynamics of mutated clone and the BCR-ABL1 transcripts, allowed to define the role of mutation in the resistance, selecting the appropriate TKI and to evaluate treatment response.\nThe analysis of LYN/PTEN expression in imatinib or nilotinib resistant patients without mutations, allowed associating the lack of response to treatment with altered expression of these genes.\nThe quantification of BCR-ABL1P190 in ALL, proved to be an important tool to evaluate treatment response and define minimum residual disease prior to bone marrow transplantation.